Child Maltreatment and Persistent Smoking From Adolescence Into Adulthood: A Birth Cohort Study. Issue 1 (15th March 2019) - Kisely, Steve; Abajobir, Amanuel Alemu; Mills, Ryan; Strathearn, Lane; Clavarino, Alexandra; Gartner, Coral; Najman, Jake Moses
Abstract: Objective: A prospective record-linkage analysis to examine whether notified and/or substantiated child maltreatment is associated with the prevalence and persistence of smoking in early adulthood. Methods: The sample consisted of 3758 participants enrolled in a population-based birth cohort study in Brisbane, Australia, who were followed up at both 14 and 21 years of age. Suspected experience of child maltreatment was measured by linkage with state child protection agency data. The two main outcomes were the prevalence and persistence of smoking at 21-year follow-up, as well as the 12-month prevalence of nicotine use disorder for participants who completed the Composite International Diagnostic Interview-Auto version. Results: Of the 3758 young people at the 21-year follow-up, 7.5% ( n = 282) had a history of notified maltreatment by the age of 16 years. Of these, 167 cases were substantiated. There were 1362 (35.3%) smokers at 21-year follow-up, although only 220 (5.9%) smoked more than 20 cigarettes daily. Of the 602 participants who smoked at 14 years, 289 were still smoking 7 years later. On adjusted analyses, participants who had experienced any form of notified and/or substantiated maltreatment were approximately twice as likely to be smokers at 21 years old and persistent smokers from 14 years of age. Any form of maltreatment, except sexual abuse, was also associated with an increase in the 12-month prevalence of nicotine use disorders. Conclusions: Child maltreatment is associated with both an increased onset and persistence of smoking from adolescence into young adulthood. This may have implications for smoking cessation programs and early interventions for individuals who have experienced maltreatment.